PERANCANGAN KOMIK PERMAINAN TRADISIONAL SIPAK TEKONG DI KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN - MELISA PUTRIADI, Drs. Syafwan, M.Si, Drs. SyafrilR, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Traditional games Sipak Tekong is the game that has been passed down by Indonesian society since the former. Forms of the game that there is nothing to hide and seek. The game is common in some parts of Indonesia, but here the authors conducted a survey in the districts Patamuan in regency Padang Pariaman Sumatera Barat. Based on the author's observation, the game Sipak Tekong has been almost forgotten by the children as more interest in the children of the modern game. And there is no better promotion of the game which is able to remind the public, especially the children that traditional game Sipak Tekong is very much useful.The design of the traditional game comics Sipak Tekong aims to remind people of tradition and culture that deserves to defended. In addition to comic media promotion is also supported by other media such as T-shirts, picture cards, pins, bags, stickers, calendars, mugs, notebooks, and candy jars. The design is based on the theory of media data analysis 5W1H, by following the path of the data analysis can be seen in detail on how to design an attractive of media for the promotion of traditional games Sipak Tekong. Based on a comic design is expected to be medium or media that is able to seize the attention of the public especially children to the traditional game pantasnya Sipak Tekong back toned.Keywords: Sipak Tekong,Tradition, Comics.